Relación entre el gasto de capital y la rentabilidad del Banco BBVA en el Perú durante el periodo 2018 – 2023 - Arteaga Arevalo, Cesar Abraham (2025)
This research analyzed the relationship between capital expenditure (CapEx) and the financial profitability of BBVA in Peru during the period 2018–2023. In a context marked by the digital transformation of the financial system and the post-pandemic economic recovery, the study aimed to determine whether the bank’s investments in technological and operational infrastructure effectively translated into improvements in its profitability indicators. A quantitative, non experimental, and correlational research design was applied, using quarterly data extracted from the bank's financial statements. Spearman's rank correlation was used to evaluate the relationship between CapEx and various profitability indicators, such as ROE, Net Financial Margin, and derived financial ratios. The findings revealed positive and statistically significant relationships in some cases, particularly between the CapEx/Income ratio and the Net Financial Margin, although short-term inverse effects were also identified in certain indicators. The study concludes that capital expenditure does impact profitability, but its effect is neither immediate nor uniform. Instead, it depends on factors such as the quality of investment, time of return, and prevailing economic conditions. Based on these results, strategic recommendations and proposals are presented to optimize CapEx management in the banking sector and improve long-term financial performance.